Aggregation-induced emission effect on turn-off fluorescent switching of a photochromic diarylethene - Kono, Luna; Nakagawa, Yuma; Fujimoto, Ayako; Nishimura, Ryo; Hattori, Yohei; Mutai, Toshiki; Yasuda, Nobuhiro; Koizumi, Kenichi; Yokojima, Satoshi; Nakamura, Shinichiro; Uchida, Kingo (Beilstein Journal of Organic Chemistry, 2019)
Background: Diarylethenes are well-known photochromic compounds, which undergo cyclization and cycloreversion reactions between open- and closed-ring isomers. Recently, diarylethene derivatives with photoswitchable fluorescent properties were prepared. They are applicable for fluorescence imaging including bio-imaging. On the other hand, a new system called “excited state intramolecular proton transfer (ESIPT)” is reported. In the system, absorption and emission bands are largely separated due to the proton transfer, hence it showed strong fluorescence even in the crystalline state. We aimed to construct the photochromic system incorporating the ESIPT mechanism.Results: A diarylethene incorporating a fluorescent moiety that exhibit ESIPT behavior was prepared. The ESIPT is one of the examples which express the mechanisms of aggregation-induced emission (AIE). This compound emits orange fluorescence with a large Stokes shift derived from ESIPT in aprotic solvents such as THF or hexane, while it exhibits only a photochromic reaction in protic solvents such as methanol. In addition, it shows turn-off type fluorescence switching in an aprotic solvent and in crystals. The fluorescence is quenched as the content of closed-ring isomers increases upon UV light irradiation.Conclusions: A diarylethene containing an ESIPT functional group was prepared. It showed fluorescent turn-off behavior during photochromism in aprotic solvents as well as in crystalline state upon UV light irradiation. Furthermore, it showed AIE in THF/water mixtures with blue-shift of the emission.
Keywords: AIE; diarylethene; ESIPT fluorescent switching; turn-off fluorescence